2009
DOI: 10.1037/a0014977
|View full text |Cite
|
Sign up to set email alerts
|

Power to the people: Using learner control to improve trainee reactions and learning in web-based instructional environments.

Abstract: This experimental study investigated the mechanisms by which learner control influences learning in an e-learning environment. The authors hypothesized that learner control would enhance learning indirectly through its effect on trainee reactions and learner engagement (in particular, off-task attention), such that learners who were more satisfied with the training and devoted more cognitive resources toward the instructional content versus off-task thoughts would possess greater posttraining knowledge. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 47 publications
4
87
1
1
Order By: Relevance
“…Kraiger and Jerden (2007) identified learner control as a useful factor high level learning engagement and for e-learning superiority. Orvis et al (2009) found that learner control has a positive impact on learning satisfaction, and that high-level learner control over the learning environment features would influence the learners' affective and utility-based reactions to these features.…”
Section: Learner Controlmentioning
confidence: 99%
“…Kraiger and Jerden (2007) identified learner control as a useful factor high level learning engagement and for e-learning superiority. Orvis et al (2009) found that learner control has a positive impact on learning satisfaction, and that high-level learner control over the learning environment features would influence the learners' affective and utility-based reactions to these features.…”
Section: Learner Controlmentioning
confidence: 99%
“…This additional dimension differentiates EL and LC training methods; LC provides learners with options to adapt the learning content to their learning style, skill, or experience; EL requires learners to discover relationships and interactions between variables through exploring the learning content. Proponents emphasize a benefit of LC to learner motivation, level of active involvement (e.g., Corbalan et al, 2009;Schnackenberg & Sullivan, 2000), and trainee satisfaction with the learning environment (Fisher, Wasserman, & Orvis, 2010;Granger & Levine, 2009;Orvis et al, 2009), which should affect learning and transfer. EL proponents argue that it encourages metacognitive activity and self-regulation of learning skills required for developing adaptable complex skills (e.g., Bell & Kozlowski, 2008;Heimbeck, Frese, Sonnentag, & Keith, 2003;Ivancic & Hesketh, 2000;Keith & Frese, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The differences in communication style might influence how men and women react to their trainer and other trainees during online communications. In addition, Web-based and hybrid courses allow the learner more control over how they learn (Orvis, Fisher, & Wasserman, 2009). This might allow women to gain more opportunity in their choice of learning tools; for example, given that women are more relational than men (Gilligan, 1982) they might prefer to interact more through online forums or chat rooms.…”
Section: Discussionmentioning
confidence: 97%